2012
DOI: 10.1002/chem.201201362
|View full text |Cite
|
Sign up to set email alerts
|

Organocatalytic Aza‐Michael–Michael Cascade Reactions: A Flexible Approach to 2,3,4‐Trisubstituted Tetrahydroquinolines

Abstract: Cascading like dominos: An efficient and highly enantioselective synthesis of 2,3,4-trisubstituted tetrahydroquinolines through cascade aza-Michael-Michael reactions was developed. Tetrahydroquinolines were obtained in excellent yields, high enantioselectivities, and good diastereoselectivities, and could be easily transformed into ring-fused tetrahydroquinolines (see scheme).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(22 citation statements)
references
References 59 publications
(2 reference statements)
0
21
1
Order By: Relevance
“…We found that the catalytic model proposed by Xu’s group could not explain our observed stereochemical result 5b. The configurations of products deduced following Xu’s model are opposite to those determined by X‐ray analysis.…”
Section: Resultscontrasting
confidence: 75%
“…We found that the catalytic model proposed by Xu’s group could not explain our observed stereochemical result 5b. The configurations of products deduced following Xu’s model are opposite to those determined by X‐ray analysis.…”
Section: Resultscontrasting
confidence: 75%
“…Tetrahydroquinoline derivatives 445 were synthesized by Xu and co‐workers in 2012 via an asymmetric domino aza‐Michael/Michael reaction between ortho ‐aminophenyl‐substituted α,β‐unsaturated ketones 64 and nitroalkenes 446 , catalyzed by a quinidine‐derived thiourea 447 (Scheme ) . Du and co‐workers later obtained the same enantiomers of 445 in high stereoselectivities using a quinine‐derived squaramide 448 as the catalyst (Scheme ) .…”
Section: Multifunctional Catalystsmentioning
confidence: 99%
“…The tricyclic backbone of compounds 5 is incorporated into Neurukin NK2 receptor antagonists, BKCa channel agonists, and liver x receptor (LXR) modulators . Compound 5b was prepared earlier as a mixture of diastereomers ( dr 87:13) from diastereomerically diverse tetrahydroquinoline 4b derived from unprotected ortho ‐aminochalcone 1′ . Using N ‐nosylated tetrahydroquinolines 3m – o , diastereomerically pure and readily attainable via the IVb ‐catalyzed asymmetric cascade reaction of 1b with 2a , 2d and 2i , respectively, we fulfilled a convenient stereospecific synthesis of compounds 4a – c and 5a – c as single diastereomers.…”
Section: Resultsmentioning
confidence: 99%